Epistemologi Sejarah Islam: Sebuah Pemetaan Kajian Sejarah Islam di Sumatera Utara - Yusra Dewi Siregar; Zainul Fuad; Laila Rohani (Local History & Heritage, 2025)
This study explores the epistemology of Islamic history within the framework of Islamic historiography in North Sumatra through academic research at Universitas Islam Negeri Sumatera Utara, Universitas Sumatera Utara, and Universitas Negeri Medan. Islamic history in this region is shaped not only by rational and empirical facts but also by intuition, revelation, and local cultural elements such as mentifacts and sociofacts, requiring an integrative epistemological approach to achieve a holistic reconstruction. Using a qualitative descriptive-analytical method, the study combines fieldwork and library research. Data were obtained from theses, dissertations, journals, books, and papers, as well as direct observation, interviews, and examinations of manuscripts and historical artifacts. Source verification was conducted through external and internal criticism, recognizing the limitations of purely empirical methods in addressing the transcendental dimensions of Islamic history. Thematic analysis was organized according to regional scope and scholarly orientation, guided by the prophetic social sciences paradigm that prioritizes ethical and spiritual values as reflected in the Qur’an (Q.S. Ali Imran: 110). Findings reveal distinct emphases: UIN focuses on religious studies and scholar biographies,  Universitas Sumatera Utara  highlights socio-cultural dynamics of the Malay community, and  Universitas Negeri Medan  displays thematic diversity shaped by students’ regional backgrounds.